Impact of COVID-19 on the Global Tourism Economy - Syaifudin, Arief; Hendarmawan, Hendarmawan; Novianti, Evi (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
COVID-19 has paralyzed the world tourism sector. Travel restrictions (land, air, and sea), quarantine policies by the competent authorities, and physical restrictions are the main factors for cessation of tourism activities. The tourism sector that relies on individual mobility is supported by transportation modes so that when this is limited, it will have an impact on decreasing tourist visits, occupancy rates and the cancellation of a number of festivals and events that are routinely held until in the end this condition has an impact on tourism sector income. This study aims to obtain an overview of the impact of COVID-19 on the income of the tourism sector in a number of countries. Through literature studies, it is hoped that sufficient information can be obtained so that it can be used as a consideration for tourism managers in developing the concept of sustainable tourism in the future.